2011
DOI: 10.1007/s10689-011-9481-7
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of BRCA1 and BRCA2 mutations in the sporadic breast cancer of Spanish population

Abstract: The true prevalence of BRCA1/BRCA2 (BRCAs) germline mutations in sporadic breast or ovarian cancer (SBC/SOC) in Caucasian population is not well established. The aim of the study is to establish the prevalence of BRCAs mutations in SBC to ponder its relevance in the programs of genetic counseling in cancer and to explore the genotype-phenotype relationship of these particular breast cancers. The study was performed in 495 SBC. We sought 46 BRCA1 and 53 BRCA2 pathogenic mutations reported in the Spanish populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…The average age of onset of BRCA1 and BRCA2 carriers in our study was similar to that in Chinese and Caucasian populations (Yip et al, 2009;Zhang et al, 2012), indicating that BRCA1/2 mutations may contribute to the early onset of breast cancer development in Kazakh women. Invasive ductal carcinoma is the most common histological subtype found among Kazakh breast cancer patients, but it was not the predominant histological tumor type in BRCA1/2 carriers in our cohort, which differed from the results observed in a Chinese Han population (de Juan Jiménez et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The average age of onset of BRCA1 and BRCA2 carriers in our study was similar to that in Chinese and Caucasian populations (Yip et al, 2009;Zhang et al, 2012), indicating that BRCA1/2 mutations may contribute to the early onset of breast cancer development in Kazakh women. Invasive ductal carcinoma is the most common histological subtype found among Kazakh breast cancer patients, but it was not the predominant histological tumor type in BRCA1/2 carriers in our cohort, which differed from the results observed in a Chinese Han population (de Juan Jiménez et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite differences in the method of collecting data, the study populations and the distributions of clinical-pathologic variables considered in our study were fundamentally consistently between the 2 hospitals. The prevalence of germline mutations in BRCA1/2 varied by ethnicity (De Leon Matsuda et al, 2002;Cherbal et al, 2012;de Juan Jiménez et al, 2012;Stadler et al, 2012;Kim and Choi, 2013;Tariq et al, 2013;Hernández et al, 2014). We observed a higher prevalence of BRCA1/2 common polymorphisms in breast cancer cases and the control group and also found that a large number of Kazakh women carried ≥ 4 co-existing BRCA1/2 alterations, which is consistent with the previously reported findings for Kazakhstan (Akilzhanova et al, 2011) and Asian and European populations (Han et al, 2006;Song et al, 2006;Loizidou et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[7,17] Our earlier studies for BRCA1 and BRCA2 mutations in breast cancer patients showed somatic missense mutation in BRCA1 gene patients, whereas no mutation was detected in BRCA2 gene. [18] In this report, considering the potential overlapping tumor suppressor role of BRCA1 and BRCA2 genes [19] and lack of any germline mutations in these genes during sporadic breast cancer, we analyzed an in situ expression of BRCA1 and BRCA2 proteins and investigated the correlation, if any, among the expression dynamics of the two proteins.…”
Section: Discussionmentioning
confidence: 97%
“…[6] Although somatic mutations have not been well characterized, loss of heterozygosity, decreased levels of BRCA1 mRNA and protein expression and methylation of the BRCA1 promoter region have been shown in some sporadic breast carcinoma, indicating the involvement of BRCA1 even in sporadic form. [7,8] Studies have indicated that the promoter region of BRCA1 gene has been found to be hypermethylated in most of the sporadic cases of breast cancer. This is indicative of interference with the expression of the gene leading to the abnormal expression of the protein.…”
Section: Introductionmentioning
confidence: 99%